Exploring the Imposter Syndrome: Perspectives from Executive Coaches - Mkhize, Nonhlanhla (University of the Witwatersrand, Johannesburg, 2025)
This study examines the role of executive coaching as an intervention to support and empower women leaders who experience imposter syndrome in South Africa. The imposter syndrome refers to a psychological phenomenon characterised by self-doubt and the persistent fear of being exposed as a "fraud." In South Africa’s corporate landscape, where women remain underrepresented in senior roles, imposter syndrome poses a significant barrier to women’s professional growth and career advancement. The purpose of this research was to explore the perceptions of executive coaches regarding their experiences in coaching women leaders affected by imposter syndrome. A qualitative, interpretivist approach was employed, with data collected through semi-structured interviews with fifteen experienced executive coaches. Thematic analysis was used to identify key themes and insights. Key findings reveal that executive coaches perceive impostor syndrome as a widespread issue affecting women’s confidence, leadership style, and career progression. Coaches identified various internal and external factors contributing to the imposter syndrome, including societal expectations and workplace dynamics. Effective coaching strategies, such as fostering self-advocacy, resilience, and reframing self-perceptions, have been found to help mitigate these effects and enable women to fully embrace their leadership potential. This study contributes to the literature by providing insights into the practical applications of executive coaching in addressing imposter syndrome, underscoring its potential as a transformative tool in developing women leaders. Recommendations for organisations include integrating executive coaching into leadership development programmes to promote gender equality in corporate leadership.
A research report submitted in fulfillment of the requirements for the Master of Management in Business and Executive Coaching, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Imposter syndrome; Executive coaching; Women leaders; SDG-3: Good health and well-being; SDG-8: Decent work and economic growth